Immunobiological Properties of Antigenic Preparations Streptococcus pneumoniae and their Mixtures - M. M. Tokarskaya; E. A. Nayаnova; O. V. Nechaeva; S. A. Baranovskaya; O. M. Afanacyeva; D. S. Vorobyev; I. M. Gruber; E. A. Astashkina; N. N. Ovechko; I. B. Semenova; N. E. Yastrebova (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. Type-specific immunity does not protect against infection with other pneumococcal serotypes. The phenomenon of the change of serotypes dominating the population of Streptococcus pneumoniae is known, in part due to the intensive recombination process and the phenomenon of «capsule switching». Therefore, the development of a serotype-independent pneumococcal vaccine is an important global public health priority. Ams. Investigation of immunobiological properties of candidate components of a future vaccine with serotype-independent activity. Materials and methods. For immunization of mice, preparations of the capsular polysaccharide of pneumococcus serotype 3 (CPS) were used; protein-containing fraction (PCF) obtained from an aqueous extract of S. pneumoniae 6B cells; recombinant pneumolysin (Ply); mixtures of drugs (CPS + Plу; CPS + PCF; PCF + Plу); conjugate vaccine Prevnar 13 (manufactured by PFIZER Inc. USA). Mice were immunized intraperitoneally, 2 times with an interval of 14 days. Intact mice were used as a control group. To assess the humoral immune IgG response, the method of solid-phase ELISA was used. Phagocytic activity was studied at 7, 14, 21 and 28 days after the second immunization. The cytokine level was determined in the blood sera of mice after the second immunization 2, 4, 8, and 24 hours later on a NovoCyte flow cytometer (ACEA Biosciences, USA) using the MACSPIex CytoKine 10 Kit mouse (Miltenyi Biotec Inc., USA) according to the manufacturer's instructions. Results. Immunization of mice with Ply as well as mixtures with CPS and PCF caused a significant increase in the level of antibodies to Ply. It was found that there was no apparent decrease in the level of antigen-specific antibodies when antigens were administered in combination with others. Pneumolysin, used alone or in combination with PCF and CPS, induces the production of antiinflammatory cytokines IL-4, IL-10, and IL-5 detected throughout the study. This is confirmed by a study of the opsonophagocytic activity of neutrophils from immunized CPS + Ply, Ply + PCF and Ply mice; a significant increase in the number of eosinophils is observed in their blood due to the stimulation of their production of IL-5. Conclusions. As a result of the studies, it was shown that Ply, used alone or in combination with CPS and PCF, has the highest immunogenicity: it stimulates a significant increase in the level of specific antibodies, stimulates Th-2, and induces the production of anti-inflammatory cytokines.